PENDIDIKAN KARAKTER TANGGUNG JAWAB DALAM PEMBELAJARAN IPS DI SMP NEGERI 30 BANJARMASIN - Johansyah Johansyah (JURNAL SOCIUS, 2019)
AbstractImages and portraits of present-day students always want something in an easy way without bothering with various processes, from the data of counseling teachers in 2016/2017 SMP Negeri 30 Banjarmasin on average each month 6% of the total number of peseta neglects responsibility, such as not doing lesson assignments, paying less attention to lessons, breaking rules, making noise in class while studying. This study uses qualitative description method, data collection using observation, documentation and interview techniques, analyzing data with data reduction, data presentation and verification, testing the validity of the data is done by triangulating the source of triangulation techniques, time triangulation, member check, extension of time and using reference materials. The results of the study state that character education is not optimal, there are still some teachers in planning learning to adopt from the internet without being analyzed and adjusted to school conditions, (2) Implementation of responsibility character education through social studies learning in Banjarmasin Public Middle 30 has not been optimal with indications that there are still participants students who do not do individual or group assignments, (3) Evaluation of character education responsibilities in SMP Negeri 30 Banjarmasin is not optimal, because some teachers have not studied the character of students in exploring and processing questions in each learning process.Keywords: Character Education, responsibility, social studies learning AbstrakGambaran dan potret peserta didik masa kini selalu menginginkan sesuatu dengan cara yang mudah tanpa bersusah payah dengan berbagai proses, dari data guru bimbingan konseling tahun 2016/2017 SMP Negeri 30 Banjarmasin rata-rata setiap bulannya 6 % dari jumlah peseta didik melalaikan tanggung jawab, seperti tidak mengerjakan tugas pelajaran, kurang memperhatikan pelajaran, melanggar tata tertib, membuat keributan di kelas saat belajar. Penelitian  ini  menggunakan metode deskripsi kualitatif, pengumpulan data dengan menggunakan teknik observasi, dokumentasi dan wawancara, analisa data dengan reduksi data, penyajian data dan verifikasi, pengujian keabsahan data dilakukan dengan trianggulasi sumber trianggulasi tehnik, trianggulasi waktu, membercheck, perpanjangan waktu dan menggunakan bahan referensi. Hasil penelitian menyatakan bahwa pendidikan karakter belum optimal, masih ada sebagian guru dalam merencanakan pembelajaran mengadopsi dari internet tanpa  dianalisis  dan disesuaikan dengan kondisi sekolah, (2) Pelaksanaan pendidikan karakter tanggung jawab melalui pembelajaran IPS Di SMP Negeri 30 Banjarmasin belum optimal dengan indikasi masih ada peserta didik yang tidak mengerjakan tugas individu maupun kelompok, (3) Penilaian  pendidikan karakter tanggung jawab di SMP Negeri 30 Banjarmasin belum optimal,dikarenakan sebagian guru belum mengkaji karakter peserta didik dalam menggali dan mengolah soal-soal dalam setiap melakukan pembelajaran.Kata Kunci: Pendidikan Karakter, tanggung jawab, pembelajaran IPS